The Sage handbook of industrial, work & organizational psychology : personnel psychology and employee performance - Ones, Deniz S., 1965-; Anderson, Neil, 1961-; Sinangil, Handan Kepir (Thousand Oaks, CA : SAGE Inc., 2017)
The first volume in The SAGE Handbook of Industrial, Organizational and Work Psychology introduces key concepts in personnel and employee performance from cognitive ability and the psychological predictors used in assessments to employee and team values. The editor and contributors present a clear overview of key research in the areas of behaviour change and how to assess individual job performance - making Volume I indispensable for anyone working in or studying Human Resource Management.
Description based on MARC record for print version.
Keywords: Psychology, Industrial